Особистісний та соціальний час як елементи філософського сприйняття темпорального виміру буття - Гуйван, П. Д.; Гуйван, Петро Дмитрович; Huivan, Petro D. (Одеса, 2021)
Наукова стаття присвячена дослідженню питання особистісного та суспільного сприйняття руху соціальних явищ у просторі і часі. Приділена значна увага вивченню часу суспільного та індивідуального. Підкреслюється, що кожне пізнання якогось процесу, матеріального об’єкта чи іншого явища пов’язане з визначенням його просторово-часових параметрів. Хоча просторово-часові форми, що їх опосередковують, виникають об’єктивно, однак усвідомлення останніх людьми в умовах суспільства стає одним із важливих чинників у науковому управлінні соціальними процесами. У роботі проаналізовано наукову теорію про розвиток часових перспектив соціальних та індивідуальних систем, їх перетинання і зіткнення, позаяк подібне вивчення дозволяє глибше вивчити феномен психологічного часу і часової перспективи як характеристик особистості. Зроблено висновок, що у сучасних умовах значення соціального аспекту в часовому рухові надзвичайно зросло. При цьому наголошується, що часове явище у кожному випадку пізнається та сприймається по-різному. Наведені спеціальні наукові та філософські спостереження, які обґрунтовують тезу, за якою точність сприйняття часу окремим суб’єктом залежить від значної кількості факторів. Також установлено, що умови професійної та творчої діяльності людини впливають на її темпоральну перцепцію. Доведено, що індивідуалізований час конкретної особи може значно відрізнятися від хронологічного. Отже, час та його сприйняття є особистісним явищем. Особа може усвідомлювати час, відчувати ритм його перебігу та зміни. Особистісна часова проблематика має велике значення у науковій розробці механізмів суспільно базової темпоральної поведінки суб’єктів та виборі адекватного інструментарію її опосередкування. При цьому окремі часові модуси щодо фізіологічних, психічних та інших процесів життєдіяльності не підконтрольні фізичній особі. Регулювання часу життя відзначається різними особистісними способами, які визначаються характером співвідношень персонального і соціального часу.

This scientific article is devoted to the study of the question of personal and social perception of the movement of social phenomena in space and time. Much attention is paid to the study of social and individual time. It is emphasized that every knowledge of a process, material object or other phenomenon is associated with the definition of its spatio-temporal parameters. And, although the space-time forms that mediate them arise objectively, the awareness of the last people in society becomes one of the important factors in the scientific management of social processes. The paper analyzes the scientific theory of the development of time perspectives of social and individual systems, their intersection and collision, as such a study allows a deeper study of the phenomenon of psychological time and time perspective as a characteristic of personality. The paper concludes that in modern conditions the importance of the social aspect in the temporal movement has increased dramatically. At the same time, it is emphasized that time as a phenomenon in each case is known and perceived differently. Specially scientific and philosophical observations are substantiated, which substantiate the thesis that the accuracy of perception of time by an individual subject depends on a significant number of factors. It is also established that the conditions of professional and creative activity of a person affect his temporal perception. It is proved that the individualized time of a particular person can differ significantly from the chronological one. Therefore, time and its perception is a personal phenomenon. A person can be aware of time, feel the rhythm of its course and change. Personality- temporal issues are of great importance in the scientific development of mechanisms of socially basic temporal behavior of subjects and the choice of adequate tools for its mediation. At the same time, certain temporal modes of physiological, mental and other life processes are not under the control of an individual. The regulation of life time is marked by various personal ways, which are determined by the nature of the ratio of personal and social timeThis scientific article is devoted to the study of the question of personal and social perception of the movement of social phenomena in space and time. Much attention is paid to the study of social and individual time. It is emphasized that every knowledge of a process, material object or other phenomenon is associated with the definition of its spatio-temporal parameters. And, although the space-time forms that mediate them arise objectively, the awareness of the last people in society becomes one of the important factors in the scientific management of social processes. The paper analyzes the scientific theory of the development of time perspectives of social and individual systems, their intersection and collision, as such a study allows a deeper study of the phenomenon of psychological time and time perspective as a characteristic of personality. The paper concludes that in modern conditions the importance of the social aspect in the temporal movement has increased dramatically. At the same time, it is emphasized that time as a phenomenon in each case is known and perceived differently. Specially scientific and philosophical observations are substantiated, which substantiate the thesis that the accuracy of perception of time by an individual subject depends on a significant number of factors. It is also established that the conditions of professional and creative activity of a person affect his temporal perception. It is proved that the individualized time of a particular person can differ significantly from the chronological one. Therefore, time and its perception is a personal phenomenon. A person can be aware of time, feel the rhythm of its course and change. Personality- temporal issues are of great importance in the scientific development of mechanisms of socially basic temporal behavior of subjects and the choice of adequate tools for its mediation. At the same time, certain temporal modes of physiological, mental and other life processes are not under the control of an individual. The regulation of life time is marked by various personal ways, which are determined by the nature of the ratio of personal and social time.
Гуйван П. Д. Особистісний та соціальний час як елементи філософського сприйняття темпорального виміру буття / П. Д. Гуйван // Актуальні проблеми філософії та соціології : Науково-практичний журнал / Голов. ред. С. Г. Секундант, відпов. ред. Д. В. Яковлев ; Міністерство освіти і науки України ; Національний університет "Одеська юридична академія". - Одеса, 2021. - Вип. 31. - С. 13-17. DOI https://doi.org/10.32837/apfs.v0i31.995
Keywords: особистісний та соціальний час; темпоральні характеристики; часові модуси; ersonal and social time; temporal characteristics; time modes; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects; Research Subject Categories::SOCIAL SCIENCES::Social sciences